Capturing magnetic bead-based arrays using perpendicular magnetic anisotropy - Hsiao, Yu-Ching (Applied physics letters, 2019)
Designing and implementing means of locally trapping magnetic beads and understanding the factors underlying the bead capture force are important steps toward advancing the capture-release process of magnetic particles for biological applications. In particular, capturing magnetically labeled cells using magnetic microstructures with perpendicular magnetic anisotropy (PMA) will enable an approach to cell manipulation for emerging lab-on-a-chip devices. Here, a Co (0.2 nm)/Ni (0.4 nm) multilayered structure was designed to exhibit strong PMA and large saturation magnetization (M s ). Finite element simulations were performed to assess the dependence of the capture force on the value of M s . The simulated force profile indicated the largest force at the perimeter of the disks. Arrays of Co/Ni disk structures of (4-7) μm diameter were fabricated and tested in a microchannel with suspended fluorescent magnetic beads. The magnetic beads were captured and localized to the edge of the disks as predicted by the simulations. This approach has been demonstrated to enable uniform assembly of magnetic beads without external fields and may provide a pathway toward precise cell manipulation methods